2019
DOI: 10.3389/fpls.2019.00966
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Plant-Parasitic Nematodes in Chickpea: Current Status and Future Perspectives

Abstract: Plant-parasitic nematodes constrain chickpea ( Cicer arietinum ) production, with annual yield losses estimated to be 14% of total global production. Nematode species causing significant economic damage in chickpea include root-knot nematodes ( Meloidogyne artiella , M. incognita , and M. javanica ), cyst nematode ( Heterodera ciceri) , and root-lesion nematode ( Pratylenchus thornei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 107 publications
(152 reference statements)
0
28
0
Order By: Relevance
“…A comprehensive list of chickpea varieties screened against P. thornei is provided in table 2. In general, it has been reported that wild chickpea exhibited higher level of resistance in comparison to of C. arietinum cultivars (Reen et al, 2019;Zwart et al, 2019).…”
Section: Resistance Sources For Rlnmentioning
confidence: 94%
“…A comprehensive list of chickpea varieties screened against P. thornei is provided in table 2. In general, it has been reported that wild chickpea exhibited higher level of resistance in comparison to of C. arietinum cultivars (Reen et al, 2019;Zwart et al, 2019).…”
Section: Resistance Sources For Rlnmentioning
confidence: 94%
“…As there are many nematode-susceptible plant species, we should make full use of poor- or non-host genotypes [ 69 , 70 , 71 ]. These are species/cultivars with genotypes that are immune, resistant, or tolerant to one or more of the PPN species.…”
Section: Exploiting Poor- or Non-host Cropsmentioning
confidence: 99%
“…and C. echinospermum P.H. Davis, which are cross-compatible with C. arietinum (Thompson et al 2011;Rodda et al 2016;Reen et al 2019;Zwart et al 2019;Ayaz et al 2021). There have been no reports on the genetic control of differences in P. thornei resistance in cultivated chickpea or its wild relatives.…”
Section: Introductionmentioning
confidence: 99%